2008
DOI: 10.1039/b810354b
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Cu(ii) and Ni(ii) with the 63–93 fragment of histone H2B

Abstract: Chromatin proteins are believed to represent reactive sites for metal ion binding. We have synthesized the 31 amino acid peptide Ac-NSFVNDIFERIAGEASRLAHYNKRSTITSRE-NH2, corresponding to the 63-93 fragment of the histone H2B and studied its interaction with Cu(II) and Ni(II). Potentiometric and spectroscopic studies (UV-vis, CD, NMR and EPR) showed that histidine 21 acts as an anchoring binding site for the metal ion. Complexation of the studied peptide with Cu(II) starts at pH 4 with the formation of the monod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
50
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 57 publications
11
50
0
Order By: Relevance
“…However, it can be characterized on the basis of its stoichiometry and stability constant. Indeed, the value log K* = −24.44 is typical for copper-peptide complexes with a {N Im , 3N − } coordination mode [35,46]. The value pK a = 8.72 which establishes the release of an additional proton from this complex is very close to the previously mentioned pK a value for the third amide deprotonation, explaining the low concentration of the CuLH − 3 species.…”
Section: Coordination Properties Of Cu(ii)-η2β 32-62 Complexesmentioning
confidence: 78%
See 4 more Smart Citations
“…However, it can be characterized on the basis of its stoichiometry and stability constant. Indeed, the value log K* = −24.44 is typical for copper-peptide complexes with a {N Im , 3N − } coordination mode [35,46]. The value pK a = 8.72 which establishes the release of an additional proton from this complex is very close to the previously mentioned pK a value for the third amide deprotonation, explaining the low concentration of the CuLH − 3 species.…”
Section: Coordination Properties Of Cu(ii)-η2β 32-62 Complexesmentioning
confidence: 78%
“…Our up to date reported results showed that both peptides form stable metal complexes, although H2B 63-93 presented a more effective binding towards Cu(II) than H2B 1-31 due to the absence of strong coordinating residues (such as, histidine or cysteine) in the latter [35,36]. These studies revealed an interesting increase in stability for the Cu(II)-H2B complexes compared to the species formed by -LAHYNK-peptide sharing the same binding sites, enhancing the importance of the side chains neighboring residues in the coordination process [33,35].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations